DIet and Health From reGIstered Trials on ClinicalTrials.gov: The DIGIT Study - Dinu, Monica; Pagliai, Giuditta; Del Bo', Cristian; Porrini, Marisa; Riso, Patrizia; Serafini, Mauro; Sofi, Francesco; Martini, Daniela; Angelino, Donato (Frontiers in Nutrition, 2022)
Background: Clinical trial registration has become a valuable tool that can be used to track the status and nature of trials conducted on a specific topic. This approach has been applied to many areas of research, but little is known about the characteristics and trends over time of clinical trials focused on diet and health. The aim of this study was to analyze diet-related clinical trials registered on the National Institute of Health “ClinicalTrials.gov” web platform in the last 10 years, to list and describe their characteristics, and to identify possible gaps to be filled in the future research. Methods: A search was performed on the ClinicalTrial.gov database. Intervention studies registered from January 2010 to December 2020, conducted on adults, with a follow-up ≥2 weeks, and evaluating the impact of different diets on all outcomes except those assessed with scales or questionnaires were considered. Results: At the end of the selection process, a total of 1,016 registered clinical trials were identified and included in the analysis. The most investigated dietary approaches were balanced diets (n=381 trials), followed by those based on a modification of macronutrients (n=288) and time-restricted feeding and intermittent fasting diets (n=140). The main measured outcomes included anthropometric parameters and body composition (57.8%), glycemic control parameters (49.7%), lipid parameters (40.1%), inflammatory markers (29.1%), blood pressure and/or heart rate (24.5%). A growing body of studies was also focused on microbiota and host metabolism (17.8%). Most studies had a duration of less than 12 weeks (~ 60%), and more than 90% of studies enrolled volunteers with overweight/obesity or other diseases. Regarding ageing, only 21 studies focused only on older adults. Conclusion: The number of studies investigating the relationship between diet and health has increased over the years. Despite the growing interest in the topic, there are some gaps such as the limited duration of most trials, the underrepresentation of some population groups and the limited number of studies for some diets that, although popular in the population, lack robust scientific evidence.